Evaluating the impact of recent rehabilitation guidelines on Opencast Coal Mine rehabilitation in Mpumalanga - Barnard, Philip (My University, 2020)
Mine rehabilitation and closure in South Africa are challenged by continuous changes to environmental and financial provision legislation as the “what to” do to sufficiently reduce the impacts of mining. These are met with much resistance from mining houses. Opinions of industry professionals suggested ways to achieve successful mine closure of which most were aimed at the mechanisms of “how to” achieve it. Encompassing “how to” guidelines for rehabilitation have been in existence since 2007 and since 1981 for opencast coal mining in South Africa. A case study was conducted on 15 opencast coal mines in Mpumalanga, South Africa to determine the relationship between guideline compliance and rehabilitation success. A qualitative assessment, based on questionnaires and multi-criteria decision analysis, was performed to compare guideline compliance for the various mines. Mines were subsequently ranked from least to best compliant. Overall rehabilitation success depends on the success of the first building blocks of rehabilitation implementation namely landform and soil reconstruction. An analytic geometry mathematical model was developed with key dimensions and areas of mine features used as input to quantitatively assess rehabilitation success of landform and soil reconstruction. The success results of each mine were plotted against their compliance ratings to produce linear trendlines for landform development, soil reconstruction and as a combination of both. The sensitivity of input variables was analysed for 22 scenarios. Trendline slopes of all the scenarios were convincingly positive indicating that better compliance yields increased rehabilitation success. It was concluded that the current status of rehabilitation could have been vastly different if the long existing “how to” do rehabilitation guidelines were followed. The benefits of applying the guidelines to existing and new mining areas are not only limited to increased rehabilitation success; it will also shape the nature and probably reduce the aggressiveness of future changes to legislation.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 2020